Islamic Boarding School Response to the Impact of COVID-19 in Maintaining the Pesantren Values - Salim, Ahmad; Dillah, Ibnu Ubay; Susilowati, Ika Tri (Universitas Muhammadiyah Yogyakarta, 2021)
The COVID-19 affects all aspects of life, including Islamic boarding schools or pesantren. These institutions are having difficulty conducting online learning activities because they are not familiar with this method. This study aims to reveal Islamic boarding schools’ response toward the impact of COVID-19 in maintaining pesantren values at Pesantren Miftahul Ulum, Subang, West Java. The study utilized the descriptive qualitative method. The respondents of this study were teachers (ustadz), students (santri), and leaders (kyai). The data were collected through observation, interviews, documentation, and online searching. The triangulation was employed as the data validity technique, and the data analysis technique used data reduction, data display, data verification, and conclusion. The result showed that pesantren responses in maintaining the pesantren values due to the impact of COVID-19 such as limiting the learning time in class, limiting the santri’s capacity per classroom, and limiting ustadz interaction with santri in the classroom. The learning process during the pandemic was carried out face-to-face and strictly adhered to the health protocol. The learning methods employed were sorogan, bandongan, and kempekan. Pesantren also internalizes morals to the students to guarantee the value.